A first-in-human, open-label, dose-escalation and dose-expansion phase I study to evaluate the safety, tolerability, pharmacokinetics/pharmacodynamics, and antitumor activity of QL1604, a humanized anti–PD-1 mAb, in patients with advanced or metastatic solid tumors - Huang, Zhiyu; Xu, Yanjun; Hong, Wei; Gong, Lei; Chen, Kaiyan; Qin, Jing; Xie, Fajun; Wang, Feng; Tian, Xin; Meng, Xiangrui; Feng, Wenlei; Li, Lingyan; et al. (Frontiers in Immunology, 2023)
Background：QL1604 is a humanized IgG4 mAb against PD-1. This first-in-human, open-label phase I study aimed to investigate the safety and tolerability and to identify the recommended doses of QL1604 for future studies. PK/PD, and preliminary antitumor activity were also assessed. Methods: Patients with advanced or metastatic solid tumors failed or had no standard therapies available were recruited. In the dose-escalation phase, patients were treated with QL1604 at 0.3, 1, 3, and 10 mg/kg intravenously Q2W in an accelerated titration with a traditional 3 + 3 design, followed by a dose expansion phase at 3 mg/kg Q2W, 3 mg/kg Q3W, and a fixed dose of 200 mg Q3W. Dose-limiting toxicities (DLTs) were assessed during the first 28 days after the first dose of study drug. AEs were graded per NCI-CTCAE Version 5.0, and antitumor activity of QL1604 was evaluated by investigators based on RECIST 1.1. Results：35 patients with advanced or metastatic solid tumors were enrolled. DLTs were reported in one patient at the 3 mg/kg Q2W dose level (grade 3 immune-mediated myositis and myasthenia gravis), and maximum tolerated dose was not reached. The most frequent treatment-related adverse events (TRAEs) (≥10%) were fatigue (37.1%), anemia (22.9%), blood TSH increased (17.1%), AST increased (17.1%), ALT increased (14.3%), WBC count decreased (11.4%), rash (14.3%), and pruritus (14.3%). Adverse events leading to discontinuation of QL1604 occurred in 3 of 35 patients (8.6%). Partial responses (PR) occurred in 7 patients, resulting in an objective response rate (ORR) of 20.0% (7/35). Single-dose of QL1604 exhibited a dose-dependent increase in the exposure ranging from 0.3 mg/kg to 10 mg/kg. Mean receptor occupancy (RO) for QL1604 at the dose of 3 mg/kg (Q2W and Q3W) and 200 mg Q3W were greater than 80% during cycle 1 after one infusion. Conclusions：QL1604 monotherapy exhibited favorable safety, PK, and signal of anti-tumor activity in patients with advanced or metastatic solid tumors and the results supported further 3 clinical studies of QL1604. Based on the safety, PK, and RO data, the recommended dosage for further clinical trials is 3 mg/kg or a fixed dose of 200 mg given every 3 weeks.